Four new Cu6S6 cluster-based coordination compounds: synthesis, crystal structures and fluorescence properties. Issue 13 (17th March 2021) - Zhou, Rui-Sha; Zhang, Xiao-Yu; Fu, Jin; Xin, Li-Dong; Jiao, Wei-Zhou; Song, Jiang-Feng
Abstract : For the first time, the Cu6 S6 clusters are connected to 1D inorganic CuCN (or CuSCN) chains through mercaptopyrimidine derivatives and obtain the extended arrays, providing a new strategy to construct the Cu6 S6 cluster-based coordination compounds. Abstract : A hexagonal prismatic Cu6 S6 cluster exhibits excellent near-infrared fluorescence properties due to its short Cu–Cu bonds, however, the construction of Cu6 S6 cluster-based compounds with extended structures is still a challenge. Here, four new Cu6 S6 cluster-based coordination compounds, formulated as Cu3 (pymt)3 (1 ), (CuCN)2 [Cu3 (mpymt)3 ] n (2 ), (CuSCN)[Cu3 (mpymt)3 ] n (3 ) and (CuCN)2 [Cu3 (dmpymt)3 ]·CH3 CN n (4 ) (Hpymt = pyrimidine-2-thiolate, Hmpymt = 4-methyl-pyrimidine-2-thione and Hdmpymt = 4, 6-dimethylpyrimidine-2-thione), have been synthesized through the reactions of mercaptopyrimidine derivatives and CuCN or CuSCN under solvo-thermal conditions and characterized by single-crystal X-ray diffraction, powder X-ray diffraction, IR spectroscopy, elemental analysis, and thermal gravimetric analysis. Single-crystal X-ray diffraction analysis reveals that compound 1 is a zero-dimensional Cu6 (pymt)6 molecule containing a distorted pseudo-hexagonal prismatic Cu6 S6 core. Compounds 2 and 4 with isomorphic frameworks but different organic linkers show a rare three-dimensional framework with nor topology constructed from Cu6 (mpymt)6 units and one-dimensional chiral [Cu(CN)] n chains; compared with compound 2, a more hydrophobic one-dimensional channel in compound 4 is observed due to the increase of the methyl groups on the pyrimidine ligand, in which acetonitrile molecules are filled in the channels of compound 4 . Compound 3 shows a rare two-dimensional layer constructed from Cu6 (mpymt)6 units and one-dimensional puckered (CuSCN) n chains. For the first time, Cu6 S6 clusters are connected to one-dimensional inorganic CuCN (or CuSCN) chains through mercaptopyrimidine derivatives to obtain extended arrays in compounds 2–4 . The crystals of compounds 1–4 in the solid state all show apparent red light emission. Compound 4 shows sensitive luminescence quenching response to nitrobenzene (NB), and the corresponding quenching constant ( K sv ) and detection limit are 2.06 × 10 3 M −1 and 9.27 ppm, respectively. This study provides a new strategy to construct Cu6 S6 cluster-based coordination polymers that have great potential in various applications such as luminescence sensing.